Introduction to analog and digital communications - Haykin, Simon S. 1931- (John Wiley & Sons, 2007)
Offers an accessible introduction to analog and digital communications and serves as an introductory treatment of communication theory. It is filled with an abundance of insightful examples, problems, and computer experiments. Throughout the text, the authors emphasize the practical relevance of the theory wherever appropriate, and keep the mathematical treatment at an easy-to-grasp level.